The translation of personal pronouns in French discourses into Indonesian - Sajarwa Sajarwa (Fakultas Sastra Universitas Negeri Malang, 2022)
The translation of personal pronouns in French discourses into IndonesianTranslation is the transfer of a message from a source-language text into an equivalent target-language text. Cultural differences between a source language and a target language always leave marks on a translation process. Language as part of culture influences the minds of its speakers, especially translators. French literary texts (as source texts) and their Indonesian translations (target texts) can provide examples of the differences between the reasoning process of French literary writers and that of Indonesian translators, particularly in the translation of pronouns with this topic being the focus of this present study. By carefully investigating how pronouns are translated in three French novels – Michael Tournier’s (1971) Vendredi ou la Vie Sauvage, Amin Maalout’s (1993) Le Rocher de Tanios, Gustave Flaubert’s (1972) Madame Bovary – this study’s analysis shows that the translation of French pronouns in literary texts into Indonesian results in various forms, namely pronouns, lexical equivalences, repetitions, and substitutions. The translation of the pronoun on, which signifies passive voice, results in equivalence in meaning despite the absence of formal correspondence, and thus conjures the Indonesian passive diatheses di- and ter-. Keywords: translation, pronoun, equivalence, correspondenceStrategi penerjemahan pronomina persona pada wacana bahasa Prancis ke dalam bahasa IndonesiaTerjemahan adalah pengalihan pesan dari teks bahasa sumber ke teks bahasa target yang sepadan. Perbedaan budaya antara bahasa sumber dan bahasa sasaran selalu meninggalkan permasalahan pada proses penerjemahan. Bahasa sebagai bagian dari budaya mempengaruhi pikiran penuturnya, terutama penerjemah. Teks sastra Prancis (sebagai teks sumber) dan terjemahan bahasa Indonesianya (teks sasaran) dapat memberikan contoh perbedaan proses nalar penulis sastra Prancis dan penerjemah Indonesia, khususnya dalam penerjemahan kata ganti, di mana topik ini menjadi fokus dalam penelitian ini. Melalui pengamatan yang mendalam terhadap tiga novel – Michael Tournier’s (1971) Vendredi ou la Vie Sauvage, Amin Maalout’s (1993) Le Rocher de Tanios, Gustave Flaubert’s (1972) Madame Bovary – analisis penelitian ini menunjukkan bahwa penerjemahan kata ganti orang bahasa Prancis dalam teks sastra ke dalam bahasa Indonesia menghasilkan berbagai bentuk, yaitu kata ganti, padanan leksikal, pengulangan, dan penggantian. Terjemahan kata ganti on, yang menandakan suara pasif, menghasilkan kesetaraan makna meskipun tidak ada korespondensi formal, dan dengan demikian memunculkan diatesis pasif bahasa Indonesia di- dan ter-.Kata kunci: terjemahan, kata ganti, padanan, kesejajaran